الاستثمار الأجنبي المباشر في الجزائر: بين نصوص القانون المحفّزة والواقع الاستثماري المعيق - حمدي, مريم; حمدي, فلة (revue mofakir; No 10 (2014): مجلـــة المفكــر, 2018)
Algeria witnesses these days an apparent financial prosperity indicated by the large improvements in the overall economic indicators, and this resulted in the improvement of the investment climate. However, the volume of foreign direct investment did not reach the level of opportunities and possibilities given, and this raises the question of the adequacy of guarantees and different incentives given by the Algerian legislature to attract more foreign investments. The realty requires an intervention to remove restrictions particularly in front of foreign direct investment. In this study, we try to diagnose the actual foreign investment in Algeria, between the mandatory legal texts, which wholly aim to create, encourage and upgrade all kinds of investments, and the corresponding investment reality which is full of obstacles and restrictions.